The Effect of Iron Slag Powder Addition on the Performance of Self-Compacting Concrete - Abu Haliga, Haifa Ali; Alebrahim, AbdulHadi Mohamed; Al-Mobaid, Hamed Munir (Journal of engineering sciences and information technology, 2025)
This study aimed to utilize iron slag as a cementitious binder in varying proportions (5%, 10%, 15%, 20%, and 25%) by weight of ordinary Portland cement (42.5 KN). To achieve this, the iron slag was ground to match the fineness of cement and subsequently replaced in the designated proportions. Laboratory experiments were conducted on self-compacting concrete to assess the impact of iron slag addition on its properties in both fresh and hardened states. In the fresh state, performance was evaluated using tests such as the slump flow test, J-Ring test, and others. In the hardened state, the compressive strength of concrete cubes was measured at different curing ages (7 and 28 days), along with the absorption test, providing insights into the relationship between permeability and concrete durability. This study contributes to industrial waste reduction by repurposing iron slag instead of disposing of it in open sites, thereby conserving vast land areas and mitigating environmental impacts. Additionally, it offers a local alternative to imported materials. Despite the use of a lower water-to-cement ratio (0.42) compared to conventional concrete (0.45–0.375), the results confirmed the efficiency of this concrete type, demonstrating satisfactory mechanical and engineering properties. The findings indicated that incorporating iron slag enhances concrete workability, reduces bleeding, and improves mix homogeneity and resistance to segregation. Moreover, its inclusion increases compressive strength by reducing permeability. The study concluded that replacing 10–15% of cement with iron slag produces high-performance concrete while minimizing environmental impact, making it a viable option for sustainable construction, particularly in heavily reinforced structures or those exposed to chemical environments.
Keywords: Self-compacting concrete; iron slag; cementitious material